Aid Allocation through Various Official and Private Channels: Need, Merit and Self-Interest as Motives of German Donors - Peter Nunnenkamp; Hannes Öhler (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2009)
Previous literature largely ignores the heterogeneity of aid channels used by each single donor country. We estimate Tobit models to assess the relative importance of recipient need, recipient merit and self-interest of donors for various channels of official and private German aid across a large sample of recipient countries in 2005-2007. Our findings strongly underscore the need for a disaggregated analysis of aid allocation. Aid channels differ significantly in the extent to which need and merit are taken into account. Yet, the German case does not reveal unambiguously superior aid channels. Better targeted aid through some channels seems to be conditioned on political support by recipient countries in the UN General Assembly.
Keywords: F35; 330; Aid Allocation; Aid Channels; Donor Motives; Germany; Tobit models